(untitled) (JURNAL ADMINISTRASI PUBLIK, 2024)
ABSTRACK This research aims to determine the Self-Efficacy of State Civil Servants at the Manado City Regional People’s Representative Council Secretariat. This analysis uses qualitative research. The informants for this research are the Secretary of the Regional People’s Representative Council, Head of Division, Head of Subdivision, ASN Employees. Information collection uses observation, interview and documentation techniques. In this research, data analysis uses data reduction, data presentation, and drawing conclusions. The research results show that the Self Efficacy of State Civil Apparatus uses three indicators, namely: (1) Magnitude (Level of Task Difficulty), based on interview data, there are still findings obtained by researchers such as the level of task difficulty. the tasks are different and there are levels; (2) General (Broad Field Behavior) At the Manado City DPRD Secretariat, existing employees, both ASN and THL, are still not disciplined when working, because there are still employees who come late to the office and there are also those who come to the office late. continue to prioritize personal interests, in this case the self-awareness and attitude of each individual or each employee in the Secretariat should be prioritized; (3) Strength (Level of Confidence or Hope) from the results of the interviews obtained by the researcher, there are several things that were obtained such as a meeting held by the Manado City DPRD Secretariat when a problem occurred, and having to wait for direction from the leadership and coordinating with employees, then an emotional approach was taken by finding out the cause of the problem that occurred. Keywords: ASN Self Efficacy, Magnitude, Generality, Strength.